PENGEMBANGAN DESA WISATA SIMBATAN-MAGETAN BERBASIS KEARIFAN LOKAL: POTENSI vs MASALAH - Mulyati, Tatik; Rohmatiah, Ahadiati; Hariyani, Anik Tri; Susilo, Hendro (Jurnal Terapan Abdimas, 2023)
Abstract. The realization of a tourist village is coveted by the residents of Simbatan Village, Nguntoronadi District, Magetan, because it has a lot of potential such as nature, culture, art, culinary and the existence of splashed batik products for people with disabilities. The development is carried out based on the 4 A concept in tourism development, namely planning of amenities, attractions, planning of facilities and infrastructure (accommodation) and increasing the carrying capacity of the community (atmosphere). The activity approach is carried out by surveying tourism potential, focus group discussions (FGD), comparative studies on tourism. Various opportunities and potentials as well as challenges and problems to develop tourism villages including internal and external potentials and problems were analyzed using SWOT analysis (Strength, Weakness, Opportunity, and Threat). The activity partners are the Kelompok Sadar Wisata (Pokdarwis), Karang Taruna and TP PKK Simbatan Village and the Kelompok Swadaya Masyarakat 'Sambung Roso' as a forum for activities for persons with disabilities. Activities start from March to September 2022. The results of the development show that at first the community did not know the concept of a tourist village, but after receiving an explanation, they were very supportive. The community through the tourism awareness group managed to identify the potential that deserves to be presented in a tourist village from the aspect of natural, cultural, artistic, culinary potential and the existence of splashed batik that is done by persons with disabilities. The community also initiates an organizing model for tourism village managers and has various activities related to attractions and infrastructure. The self-help group “Sambung Roso” which accommodates persons with disabilities also has activities to support the establishment of a tourist village. Community support is quite high in the form of participation and has the hope that the existence of a tourist village can improve the welfare of the Simbatan residents. Abstrak. Terwujudnya desa wisata didambakan oleh penduduk Desa Simbatan, Kecamatan Nguntoronadi, Magetan, karena banyak potensi yang dimiliki seperti alam, budaya, kesenian, kuliner dan keberadaan batik ciprat produk penyandang disabilitas. Pengembangan dilakukan berdasarkan konsep 4 A dalam pengembangan wisata yaitu perencanaan amenitas, atraksi, perencanaan sarana-prasarana (akomodasi) dan peningkatan daya dukung masyarakat (atmosfer). Pendekatan kegiatan dilakukan dengan survei potensi wisata, focus group discussion (FGD), studi banding wisata. Berbagai peluang dan potensi serta tantangan dan permasalahan untuk mengembangkan desa wisata termasuk potensi dan permasalahan internal maupun eksternal dianalisis menggunakan analisis SWOT (Strenght, Weakness, Opportunity, dan Threat). Mitra kegiatan adalah Kelompok Sadar Wisata (Pokdarwis), Karang Taruna dan TP PKK Desa Simbatan serta Kelompok Swadaya Masyarakat ‘Sambung Roso’ sebagai wadah kegiatan penyandang disabilitas. Kegiatan dimulai sejak Maret hingga September 2022. Hasil pengembangan menunjukkan bahwa pada awalnya masyarakat belum mengetahui konsep desa wisata, tetapi setelah memperoleh penjelasan, meraka sangat mendukung. Masyarakat melalui kelompok sadar wisata berhasil mengindentifikasi potensi yang layak disajikan dalam desa wisata dari aspek potensi alam, budaya, kesenian, kuliner dan keberadaan batik ciprat yang dikerjakaan oleh penyandang disabilitas. Masyarakat juga memprakarsai model pengorganisasian pengelola desa wisata serta memiliki berbagai kegiatan terkait atraksi dan sarana prasarana. Kelompok swadaya masyarakat “Sambung Roso” yang mewadai penyandang disabilitas juga memiliki kegiatan untuk mendukung terwujudnya desa wisata. Dukungan masyarakat cukup tinggi dalam wujud partisipasi dan memiliki harapan bahwa keberadaan desa wisata dapat meningkatkan kesejahteraan penduduk Simbatan.